2013
DOI: 10.2147/ijwh.s52429
|View full text |Cite
|
Sign up to set email alerts
|

Burden of menstrual symptoms in Japanese women – an analysis of medical care-seeking behavior from a survey-based study

Abstract: BackgroundMenstrual symptoms are associated with various health problems in women of reproductive age, and this may impact their quality of life. Despite this, Japanese women are likely to hesitate seeking a specialist’s medical help for their menstrual symptoms.PurposeTo study subject parameters including symptom severity, gynecological disorders, and treatments in medical care-seeking women (outpatient) and women opting for self-care (nonvisit), to identify reasons why Japanese women do not see a gynecologis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
69
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(79 citation statements)
references
References 16 publications
7
69
3
Order By: Relevance
“…The age distribution in the current study was highly similar to other cross-sectional survey studies on dysmenorrhea in Japan 57,15. A larger proportion of participants in this study were employed (full time, part time, or self-employed) than in the two studies that reported on this variable,5,6 although the annual household income distribution in the current study was in line with a study by Tanaka et al5 Most participants in this study had normal BMI, whereas the majority of participants in a study by Nohara et al were underweight 7.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The age distribution in the current study was highly similar to other cross-sectional survey studies on dysmenorrhea in Japan 57,15. A larger proportion of participants in this study were employed (full time, part time, or self-employed) than in the two studies that reported on this variable,5,6 although the annual household income distribution in the current study was in line with a study by Tanaka et al5 Most participants in this study had normal BMI, whereas the majority of participants in a study by Nohara et al were underweight 7.…”
Section: Discussionsupporting
confidence: 88%
“…The age distribution in the current study was highly similar to other cross-sectional survey studies on dysmenorrhea in Japan 57,15. A larger proportion of participants in this study were employed (full time, part time, or self-employed) than in the two studies that reported on this variable,5,6 although the annual household income distribution in the current study was in line with a study by Tanaka et al5 Most participants in this study had normal BMI, whereas the majority of participants in a study by Nohara et al were underweight 7. Additionally, OTC analgesic use in this study was moderately higher than that of outpatients, as well as women in the general population, with dysmenorrhea in studies by Tanaka et al,5,6 yet much lower than the OTC analgesic use reported by women with dysmenorrhea who did not seek medical treatment 5.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Regardless of the cause, dysmenorrhea can have a substantial impact on patient quality of life,7,8 yet many patients do not seek treatment 9. In a patient survey, some untreated women have expressed feelings of resistance or aversion toward seeking therapy, and many suggested that gynecologist consultations were unnecessary for their disorder 1. However, a substantial proportion of women who did seek medical treatment agreed that their daily lives were significantly improved after therapy, and it was also estimated that gynecologist visits saved over 7,000 JPY (70 USD) monthly costs per-patient, occurring due to time off work 1…”
Section: Introductionmentioning
confidence: 99%